Synthesis and Antimicrobial Activity of Some 1,5-Dioxadiazolyl/Ditriazolyl and Dipyrrolylindole Derivatives - G. Bhovi, Manjunath; S. Gadaginamath, Guru (Asian Journal of Chemistry, 2016)
The exclusive formation of dicarbohydrazide 3 from the indole triester 2 revealed the chemoselectivity of esters at positions 1 and 5 over that of C3-ester towards nucleophilic attack of hydrazine hydrate. This indole dicarbohydrazide 3 was reacted separately with CS2/KOH, acetonyl acetone, CS2, KOH/N2H2·H2O and isothiocyanates to secure 1-(5-mercapto-1,3,4-oxadiazol-2-yl)-methyl-3-ethoxy-carbonyl-5-(5-mercapto-1,3,4-oxadiazol-2-yl)methoxy-2-methylindole 5, 1-(2,5-dimethyl-pyrrol-1-yl)aminocarbonylmethyl-3-ethoxycarbonyl-5-(2,5-dimethyl-pyrrol-1-yl)aminocarbonylmethoxy-2-methylindole 6, 1-(4-amino-5-mercapto-1,2,4-triazol-3-yl)methyl-3-ethoxycarbonyl-5-(4-amino-5-mercapto-1,2,4-triazol-3-yl)methoxy-3-ethoxycarbonyl-2-methylindole 7 and 1-(N-substituted thiosemicarbazinocarbonyl)methyl-3-ethoxycarbonyl-5-(N-substituted thiosemicarbazinocarbonyl)methoxy-2-methylindoles 8a-b respectively. The thiosemicarbazzides 8a-b were heated with 4% NaOH to produce 1-(4-substituted-5-mercapto-1,2,4-triazol-3-yl)methyl-5-(4-substituted-5-mercapto-1,2,4-triazol-3-yl)methoxy-2-methylindole-3-carboxylic acids 9a-b. All these new compounds were screened for their antimicrobial activity.